Chemical Structure of Cassia auriculata Linn. Seeds Polysaccharide - Singh, R.B. (Asian Journal of Chemistry, 2010)
Acid hydrolysis of fully methylated water soluble Cassia auriculata Linn. seeds produced certain important medicinal chemicals. On the basis of obtained results a tentative structure has been assigned to the seeds polysaccharide.